EFEKTIVITAS PELAKSANAAN PLP 2 TERHADAP KESIAPAN MENJADI GURU PADA MAHASISWA PENDIDIKAN BAHASA DAN PENDIDIKAN KEPELATIHAN OLAHRAGA - Tabrani Rasyid, Andi; Syahrani, Neza; Sanatang; Jumarni; Sherli; Ayuni Binti Syamsuddin, Nurul; Anwar, Aril; Syahrullah, Ali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of the implementation of the School Field Introduction Program II (PLP II) on the readiness of Language Education and Sports Coaching Education students to become professional teachers. This research used a qualitative descriptive approach. The subjects of the study consisted of students participating in PLP II from three study programs. Data were collected through observation, interviews, and documentation. The data were analyzed using the interactive model of Miles and Huberman, including data reduction, data presentation, and conclusion drawing. The results showed that PLP II had a significant effect on improving students’ readiness to become teachers, especially in pedagogical competence, classroom management, communication skills, leadership, self-confidence, and learning evaluation. Language education students experienced improvement in communication skills, literacy-based learning, and interactive teaching methods. Meanwhile, sports coaching education students showed increased competence in managing field practice, discipline, leadership, and physical learning strategies. However, several obstacles were still found, such as limited practice time, differences in mentor guidance quality, and unequal student readiness. Overall, PLP II was considered effective in preparing prospective teachers through direct teaching experience in schools and helping students adapt to real educational environments.